Diversification Of Processed Strawberry Products To Increase The Income Of Strawberry Farming Groups In Limapuluh Kota District - Fiana, Risa Meutia; Murtius, Wenny Surya (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
The constraints in strawberry cultivation, namely its perishable nature has a very short shelf life. Processing strawberries into jams and sweets can increase the shelf life, selling value of strawberries and is easy to develop on a household scale. The implementation method carried out is counseling, training and guidance. The purpose of this activity is to increase the knowledge of strawberry farmers regarding standard operating procedures for strawberry cultivation and increase the knowledge and skills of strawberry farmers in Nagari Tanjung Aro Sikabu, Luak District, Lima Puluh Kota Regency, West Sumatra regarding the processing of strawberries into jams and sweets.The results of the activity are increasing the knowledge of the community in Limapuluh Kota Regency on processed strawberry products that can increase the added value of strawberries and can improve the community of Nagari Tanjung Aro Sikabu, Luak District, Lima Puluh Kota Regency.